DEMOGRAPHIC CHANGES IN GENDER AND AGE OF POPULATION AND THEIR IMPACT ON CONTEMPORARY BUSINESS ENVIRONMENT IN SERBIA - Berber, Nemanja; Đurić Kuzmanović, Tatjana (International Journal of Economic Practice and Policy, 2017)
Demographic changes are caused by different factors - economic, political, environmental, health, migration, etc. Demographic changes, observed through changes in gender and age of the population, largely affect changes of the business environment and work in modern organizations. The former organizational structure, business rules, norms of behaviour, work processes and behaviour of people are no longer adequate, that is, they cannot be automatically implemented in the new conditions. In order to prepare societies, states and business organizations for this new situation, it is important to explore and became familiar with the changes that are happening and with possible impact they could have on the business surrounding on particular levels of management. The aim of this paper is to explore the most significant changes that have occurred in business surroundings in terms of population by sex and age, and to explain the most important possible impacts of these changes on a global, national and organizational level. The authors have paid special attention to the analysis of long term structural changes, these impacts at the organizational level, and how organizations can change their structures and processes to more successfully manage the new workforce contingent.